Exposição a odores sociais: efeitos sobre a neurogênese adulta e a atividade neuronal de camundongos C57BL/6J machos - Thomaz Lüscher Dias (2015)
Rodents, such as mice and rats, recognize conspecifics from social odors present in each individual’s urine. This ability is referred to as social memory or social recognition. It is established that social isolation leads to a social memory deficit in mice and that environmental enrichment by social odors – feces and urine from other mice placed in the cage bedding – prevents this deficit. Other forms of environmental enrichment lead to better performance in declarative memory tasks and increase adult neurogenesis in the Hippocampus and Olfactory Bulb of control mice. The new neurons that are born in the adult brain seem to have a crucial function in the establishment of new memories. Nevertheless, it has not been demonstrated whether the protective effect of environmental enrichment by social odors on social memory happens at the same time as an increase in the number of newborn neurons in the brain. Moreover, the brain structures activated during social memory processing are not fully described yet, and there is special doubt about whether the Hippocampus plays any important role in it. Thus, the main goal of this work was to access the effect of prolonged social odor presentation (environmental enrichment) on the adult neurogenesis of socially isolated mice and the effect of brief presentation of social odors (social encounter) on the neuronal activation pattern of control mice. In order to do that, we performed BrdU and NeuN immunofluorescence to quantify the number of new neurons born in the Hippocampus and Olfactory Bulb of one week socially isolated mice kept in an environment enriched by social odors and c-Fos immunohistochemistry to quantify the number of activated neurons in several brain regions of control mice presented to an unknown set of social stimuli (novel juvenile). The obtained results show that one week social isolation increased proliferation in the Hippocampus, but that a lower percent of the newborn cells became differentiated into neurons compared to grouped house mice. Environmental enrichment by social odors was able to prevent this effect. No differences were seen in the Olfactory Bulb. The presentation of an unknown juvenile triggered differential neuronal activation only in the Basolateral and Medial posterodorsal nuclei of the Amygdala, but not in any of the Hippocampal regions accessed. These results demonstrate that social isolation alters how new cells proliferate and differentiate in the Hippocampus, but not the Olfactory Bulb, and that social odor environmental enrichment avoids such alterations in the same manner as it does on the social memory deficit cause by social isolation. However, neuronal activity detection by c-Fos immunoreaction results reveal that the Hippocampus is not differentially activated by an unknown set of social stimuli, but that the Amygdala is. This might indicate that the Hippocampus does not play a crucial role in the first stages of social memory formation.